2022
DOI: 10.1177/0272989x221104094
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges When Using the Electronic Health Record for Practice-Integrated Patient-Facing Interventions: The e-Assist Colon Health Randomized Trial

Abstract: Background Even after a physician recommendation, many people remain unscreened for colorectal cancer (CRC). The proliferation of electronic health records (EHRs) and tethered online portals may afford new opportunities to embed patient-facing interventions within clinic workflows and engage patients following a physician recommendation for care. We evaluated the effectiveness of a patient-facing intervention designed to complement physician office-based recommendations for CRC screening. Design Using a 2-arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The findings in the Lafata et al (2022) study regarding Black adults are worrisome in that African Americans exhibit higher cancer death rates and lower survival rates compared with other racial or ethnic groups (DeSantis, Miller, Goding Sauer, Jemal, & Siegel, 2019). Roy et al (2021) found that strategies to increase stool blood testing in African Americans include standard mailed blood stool tests augmented by patient navigation, tailored educational materials, and follow-up calls or mailings to increase trust in the patient–provider relationship.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in the Lafata et al (2022) study regarding Black adults are worrisome in that African Americans exhibit higher cancer death rates and lower survival rates compared with other racial or ethnic groups (DeSantis, Miller, Goding Sauer, Jemal, & Siegel, 2019). Roy et al (2021) found that strategies to increase stool blood testing in African Americans include standard mailed blood stool tests augmented by patient navigation, tailored educational materials, and follow-up calls or mailings to increase trust in the patient–provider relationship.…”
mentioning
confidence: 99%
“…Relative to online notification of CRC screening, Lafata et al (2022) found that only 28% of adults have an activated portal account through their primary care physician. In addition, Black adults are substantively and significantly less likely to have an active portal account, which limits the usefulness of this tool for delivery of screening reminders to this population.…”
mentioning
confidence: 99%
“…Above and beyond the intervention’s impact assessment, reported findings stress how the advantages afforded by developed EHR systems, in terms of embedding patient-facing interventions within clinical practice, are still in part offset by a programme effectiveness diminished by the uneven coverage of EHR tools of the target population. 4…”
mentioning
confidence: 99%